Endoscopic closure versus surgical revision in the management of gastro-gastric fistula following Roux-en-Y gastric bypass - Dolan, Russell D.; Jirapinyo, Pichamol; Maahs, Ethan D.; Thompson, Christopher C. (Endoscopy International Open, 2023)
Background and study aims Gastro-gastric fistulae (GGF) occur in 1.3 % to 6 % of Rouxy-en-Y gastric bypass (RYGB) patients and can be associated with abdominal pain, reflux, weight regain and onset of diabetes. Endoscopic and surgical treatments are available without prior comparisons. The study aim was to compare endoscopic and surgical treatment methods in RYGB patients with GGF.Patients and methods A retrospective matched cohort study of RYGB patients who underwent endoscopic closure (ENDO) or surgical revision (SURG) for GGF. One-to-one matching was performed based on age, sex, body mass index and weight regain. Patient demographics, GGF size, procedural details, symptoms and treatment-related adverse events (AEs) were collected. A comparison of symptom improvement and treatment-related AEs was performed. Fisher’s Exact, t-test and Wilcoxon Rank Sum tests were performed.Results Ninety RYGB patients with GGF (45 ENDO, 45 matched SURG) were included. GGF symptoms included weight regain (80 %), gastroesophageal reflux disease (71 %) and abdominal pain (67 %). At 6 months, the ENDO and SURG groups experienced 0.59 % and 5.5 % total weight loss (TWL) (P = 0.0002). At 12 months, the ENDO and SURG groups experienced 1.9 % and 6.2 % TWL (P = 0.007). Abdominal pain improved in 12 (52.2 %) ENDO and 5 (15.2 %) SURG patients at 12 months (P = 0.007). Diabetes and reflux resolution rates were similar between groups. Treatment-related AEs occurred in four (8.9 %) ENDO and 16 (35.6 %) SURG patients (P = 0.005), of which none and eight (17.8%), respectively, were serious (P = 0.006).Conclusions Endoscopic GGF treatment produces greater improvement in abdominal pain and fewer overall and serious treatment-related AEs. However, surgical revision appears to yield greater weight loss.